KENDALA PENEGAKAN HUKUM TINDAK PIDANA KORPORASI DALAM BIDANG PERPAJAKAAN DI INDONESIA - Dr.Bambang Ali Kusumo,S.H,Mhum. (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2021)
The subject of Tax Law is an individual (person) and a Legal Entity or Corporation. In the enforcement of tax law, there are often deviations from the Tax Law, both committed by individuals and corporations. Efforts to resolve these irregularities for person actors are easier to resolve in accordance with applicable law, but for corporate actors there are many obstacles. What is this obstacle, is revealed through research. The research was carried out with the type of juridical nomative research, the nature of the research was descriptive. The dominant data source is secondary data, which includes primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the obstacles that arise in law enforcement against corporations are caused by weaknesses in legal substance, weaknesses in legal structures, weaknesses in legal culture and weaknesses in procedural law.